Growth of science in activated sludge modelling – a critical bibliometric review - Markus Ahnert; Peter Krebs (Water Science and Technology, 2021)
In this paper, the tool of bibliometric analysis is applied to the field of activated sludge modelling and its suitability as a first step of a literature analysis is assessed. The analysis is applied to the total dataset considered as well as a time-based classification. It can be shown that this tool is very well suited to filtering the relevant authors and publications, thus enabling a subsequent visual review. The methodology presented can also be applied to sub-disciplines or other subject areas. However, the sole use of the multiple statistical and visual tools is critically questioned. Thus, misinterpretations and apparent findings can result from structural problems in the data or parameters used. Not all of the metrics used are suitable for finding relevant publications, but rather for ranking the criteria studied. However, the latter represents the most widespread application of bibliometrics. From the analysis of the keywords, it could be deduced that there has been a temporal shift from fundamental model aspects to detailed questions such as the integration of sorption and adsorption processes or anaerobic digestion. The modelling of biological phosphorus removal has also surprisingly lost a great amount of importance in the scientific literature. HIGHLIGHTS First application of a bibliometric analysis in the field of activated sludge modelling with specific guidance for implementation.; Demonstration that the tool can be used to analyse very clear trends in research based on time-dependent measures.; Evidence of the importance of using such a tool in analysing the diversity of information available today in combination with professional expertise by users.;